2021
DOI: 10.3389/fmicb.2021.637213
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Sigma Factor RpoE2 Is Involved in the Stress Response to Hypochlorite and in vivo Survival of Haemophilus influenzae

Abstract: Extracytoplasmic function (ECF) sigma factors underpin the ability of bacteria to adapt to changing environmental conditions, a process that is particularly relevant in human pathogens that inhabit niches where human immune cells contribute to high levels of extracellular stress. Here, we have characterized the previously unstudied RpoE2 ECF sigma factor from the human respiratory pathogen H. influenzae (Hi) and its role in hypochlorite-induced stress. Exposure of H. influenzae to oxidative stress (HOCl, H2O2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Traditionally, this type of enzyme has been associated with bacterial energy generation under anaerobic conditions as catalysis uses quinols that mediate electron transfer between respiratory chain complexes as the electron donors ( Kappler and Schaefer, 2014 ; Kappler et al, 2019 ). At present, only a single hypochlorite-responsive regulator, the RpoE2 extracytoplasmic function—sigma factor, has been identified in H. influenzae ( Nasreen et al, 2021 ), and this regulator might mediate the hypochlorite-based induction of dmsABC expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, this type of enzyme has been associated with bacterial energy generation under anaerobic conditions as catalysis uses quinols that mediate electron transfer between respiratory chain complexes as the electron donors ( Kappler and Schaefer, 2014 ; Kappler et al, 2019 ). At present, only a single hypochlorite-responsive regulator, the RpoE2 extracytoplasmic function—sigma factor, has been identified in H. influenzae ( Nasreen et al, 2021 ), and this regulator might mediate the hypochlorite-based induction of dmsABC expression.…”
Section: Discussionmentioning
confidence: 99%
“…S-oxide reductases are enzymes that can reverse sulfoxide-formation on biomolecules, including proteins, sulfur-containing amino acids and vitamins such as methionine, cysteine and biotin that are highly susceptible to oxidative damage ( Baltes et al, 2003 ; Denkel et al, 2013 ; Dhouib et al, 2016 , 2021 ; Ezraty et al, 2017 ; Kappler et al, 2019 ; Zhong et al, 2020 ; Nasreen et al, 2021 ). S-oxide reductases are emerging as essential components for virulence and fitness of bacterial pathogens such as Escherichia coli , Salmonella sp., Actinobacillus pleuropneumoniae , and Haemophilus influenzae ( Baltes et al, 2003 ; Denkel et al, 2013 ; Dhouib et al, 2016 , 2021 ; Ezraty et al, 2017 ; Kappler et al, 2019 ; Zhong et al, 2020 ; Nasreen et al, 2021 ), where a loss of S-oxide reduction causes a reduction of survival in infection models.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of both mtsZ and msrAB was induced by exposure of the bacteria to hypochlorite and is controlled by an extracytoplasmic function sigma factor, RpoE2, that is conserved in H. influenzae strains. In keeping with this observation, MsrAB is required for the hypochlorite resistance of H. influenzae [ 16 , 18 ]. MsrAB was also involved in host immune response modulation, where in response to infections with an H. influenzae msrAB strain, higher levels of expression of antimicrobial peptides were observed, while expression of the antiapoptotic XIAP protein was reduced [ 18 ].…”
Section: Introductionmentioning
confidence: 96%
“…We have recently characterized three enzymes involved in MetSO reduction in the H. influenzae periplasm, the molybdenum enzymes DmsABC and MtsZ and the MsrAB methionine sulfoxide reductase that contains both an MsrA and MsrB domain [ 16 , 17 , 18 , 19 ]. Both of the molybdenum-containing enzymes were able to reduce free MetSO; however, expression levels of DmsABC were significantly lower than for MtsZ, which appears to be the major molybdenum-dependent methionine sulfoxide reductase in H. influenzae strain Hi2019 [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating H. influenzae oxidative stress resistance have identified numerous enzymes that contribute to protection that include catalase ( hktE ) and peroxiredoxin ( pgdX ), which degrade H 2 O 2 and alkyl hydroperoxides; the DNA-binding ferritin-like protein ( dps ); three periplasmic methionine sulfoxide reductases ( torZ , msrAB, dmsABC ); and a manganese (Mn) superoxide dismutase ( sodA ). In addition, key regulators that control responses to oxidative stress have also been identified that include those for H 2 O 2 exposure (OxyR), perturbation of iron (Fe) homeostasis (Fur, ferric uptake regulator), and reactive chlorine species-induced stress, such as HOCl (alternative sigma factor RpoE2). Nevertheless, there remain unexplored aspects of H. influenzae oxidative stress tolerance such as Mn homeostasis, which has a prominent contribution to bacterial stress responses and has recently been shown to have important roles in H.…”
mentioning
confidence: 99%